DYNAMIC FIRMNESS OF BOTTOM OF BORING COLUMN WITHOUT INTERMEDIATE AND WITH INTERMEDIATE ELEMENTS IN ARRANGEMENT - Мойсишин, Василь Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The author formulates and solves problems of dynamic stability of a bottom-hole drill string assembly with intermediation devices (support-centring devices, shock-absorbers) and without them.